The Development of Pop-Up Book-Based Learning Media for Hajj and Umrah Procedures - Utin Mutia; Rudini Rudini (FKIP - Universitas Riau, 2026)
The urgency of this research is to develop a pop-up book as a learning media to support the teaching of Hajj and Umrah procedures. Based on initial interviews conducted by researchers at several high schools in Central Bangka Regency with teachers of religious education, there are no adequate facilities and infrastructure for practicing Hajj rituals for Hajj material. However, Hajj is one of the obligatory acts of worship for Muslims and must be known by high school students who are Muslim, just as they must know other obligatory acts of worship such as prayer and fasting. This study adopts a research and development (R&D) method using the Dick and Carey model, which includes; (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Validation from media experts indicated that the developed media is valid and feasible for use. The results of this study showed a significant increase in students' learning outcomes based on the average of comparison scores between pretest 29.5 and posttest 56.25. In addition, the media was rated effective in enhancing students’ motivation and understanding of the material. Therefore, the pop-up book is considered an effective learning medium for teaching the Hajj and Umrah procedures.